Impact of aluminium oxide nanoparticles as an additive in diesel-methanol blends on a modern DI diesel engine. (25th February 2021) - Wei, Jiangjun; Yin, Zenghui; Wang, Chunmei; Lv, Gang; Zhuang, Yuan; Li, Xiangrong; Wu, Han
Highlight: The presence of nano-AL2 O3 in fuel increased the engine peak CGP and HRR. Nano-AL2 O3 additives promoted an earlier initiation and shorter combustion duration. Increasing nano-AL2 O3 content in fuel increased BTE and lessened BSFC and BSEC. Nano-AL2 O3 inclusion in fuel can suppress significantly CO, HC and smoke emissions. Conjoint use of methanol and nano-AL2 O3 in diesel is promising in real applications. Abstract: The development of nanotechnology makes nanoparticle additives for internal combustion engines possible and the existing research results have shown that the engine performances can be improved with metal-based nanoparticles additive in the fuel. The present study makes an attempt to add aluminium oxide (AL2 O3 ) nanoparticles (25, 100 ppm) into diesel-methanol blends, and to study the impact of the nanoparticle additive on the characteristics of a modern DI diesel engine. The results showed that the presence of AL2 O3 nanoparticles in the diesel-methanol blends improved the peak in-cylinder pressure, heat release rate and brake thermal efficiency by 2.5%, 16.1% and 3.6%, respectively, as compared with those without AL2 O3 additives, as well as the decreases in the ignition delay and combustion duration by up to 6.9% and 16%. And the brake specific fuel and energy consumption can be reduced by up to 3.7% and 3.5%, respectively. Moreover, engine emission tests showed the suppressions in CO, HC and smoke emissions by up to 83.3%, 40.9% and 69.2%, respectively, but a marginal increase in NOX emission by 14.4%. These results indicate that the presence of nanoparticle additives in the diesel-methanol blends can achieve sound effects of energy conservation and emission reductions.